Globalisation, technology and global health - Olatunji Abdul Shobande; Lawrence Ogbeifun; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
This study explored whether globalisation and technology are harmful to health for a global panel dataset of 52 countries for the period of 1990-2019. The study focused on four continents: Africa, the Americas, Asia/Oceania, and Europe. We used four advanced econometric methodologies, which include the standard panel fixed effect (FE), ArellanoBover/Blundell-Bond dynamic panel analysis, Hausman-Taylor specification, and Two-Stage Least Squares (FE-2SLS)/Lewbel-2SLS approach. Our empirical evidence highlights the significance of globalisation and technology in promoting global health. Our findings are not only of interest because it suggests that globalisation has varied impact on global health indicators, but they indicate that technology is useful in tracking, monitoring, and promoting global health. In addition, our empirical evidence indicates that a truly health-centered process of globalisation and technological innovation can only be realised by ensuring that the interests of countries and vulnerable populations to health risks are adequately considered in international decision-making regarding global economic integration. We suggest that achieving the aspiration of global health will entail the use of globalisation and information technology to extend human activities and provide equal access to global health.
Keywords: C52; O38; O40; O55; P37; 330; globalisation; technology; global health